Metabolism of Oxycodone in Human Hepatocytes from Different Age Groups and Prediction of Hepatic Plasma Clearance - Korjamo, Timo; Tolonen, Ari; Ranta, Veli-Pekka; Turpeinen, Miia; Kokki, Hannu (Frontiers in Pharmacology, 2012)
Oxycodone is commonly used to treat severe pain in adults and children. It is extensively metabolized in the liver in adults, but the maturation of metabolism is not well understood. Our aim was to study the metabolism of oxycodone in cryopreserved human hepatocytes from different age groups (3 days, 2 and 5 months, 4 years, adult pool) and predict hepatic plasma clearance of oxycodone using these data. Oxycodone (0.1, 1 and 10 µM) was incubated with hepatocytes for 4 hours, and 1 µM oxycodone also with CYP3A inhibitor ketoconazole (1 µM). Oxycodone and noroxycodone concentrations were determined at several time points with liquid chromatography-mass spectrometry. In vitro clearance of oxycodone was used to predict hepatic plasma clearance, using the well-stirred model and published physiological parameters. Noroxycodone was the major metabolite in all batches and ketoconazole inhibited the metabolism markedly in most cases. A clear correlation between in vitro oxycodone clearance and CYP3A4 activity was observed. The predicted hepatic plasma clearances were typically much lower than the published median total plasma clearance from pharmacokinetic studies. In general, this in vitro to in vivo extrapolation method provides valuable information on the maturation of oxycodone metabolism that can be utilized in the design of clinical pharmacokinetic studies in infants and young children.